2011
DOI: 10.1111/j.1574-6968.2011.02252.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterization of Streptococcus pyogenes isolated from patients with multiple onsets of pharyngitis

Abstract: Streptococcus pyogenes causes a broad spectrum of acute infections and is the bacterium most frequently isolated from patients with pharyngitis. A number of antibiotics including penicillin have been shown to be effective, although antibiotic treatment failure in cases of streptococcal pharyngitis have been reported. Herein, we aimed to elucidate the features of recurrent strains using clinical isolates. Ninety-three S. pyogenes organisms were obtained from Japanese patients with recurrent pharyngitis. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…It is believed that the Streptococcus pyogenes , a kind of group A streptococci, is uniformly susceptible to penicillin. However, in a paper reporting the epidemiological characteristics of S. pyogenes recovered from patients with multiple onsets of pharyngitis, two S. pyogenes isolates were shown to be highly resistant to penicillin G (MIC, 2 μg/ml) 121 . If such penicillin‐resistant S. pyogenes emerged, it would become a serious clinical problem, and therefore, we carefully checked the penicillin MICs for 256 clinical isolates of S. pyogenes using the agar dilution method in accordance with the recommendation of the CLSI.…”
Section: Other Interesting Findings and Insightsmentioning
confidence: 99%
“…It is believed that the Streptococcus pyogenes , a kind of group A streptococci, is uniformly susceptible to penicillin. However, in a paper reporting the epidemiological characteristics of S. pyogenes recovered from patients with multiple onsets of pharyngitis, two S. pyogenes isolates were shown to be highly resistant to penicillin G (MIC, 2 μg/ml) 121 . If such penicillin‐resistant S. pyogenes emerged, it would become a serious clinical problem, and therefore, we carefully checked the penicillin MICs for 256 clinical isolates of S. pyogenes using the agar dilution method in accordance with the recommendation of the CLSI.…”
Section: Other Interesting Findings and Insightsmentioning
confidence: 99%
“…Nine primer sets was used for the detection of oral streptococci, including Streptococcus mitis , Streptococcus salivarius , Streptococcus sanguinis , Streptococcus oralis , Streptococcus gordonii, Streptococcus mutans , Streptococcus sobrinus , Streptococcus pyogenes and Streptococcus pneumoniae , as previously described. 4,5,6,7 The PCR products were stained with ethidium bromide and analyzed using 1.5% agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…In the past few decades, penicillin has been used as the first-line drug for GAS infections in most parts of the world and there is no better choice. However, the study of penicillin-resistant Streptococcus pyogenes is rapidly and world-widely reported [6,7]. Therefore, more effects are needed to find new drugs for treatment of GAS infections.…”
Section: Introductionmentioning
confidence: 99%